Javanese phonological influence on English segmental sound production: A qualitative case study - Nevy Alexia; Hanandyo Dardjito (Universitas Sarjanawiyata Tamansiswa, 2026)
This study identifies the English segmental pronunciation patterns produced by a Javanese-speaking EFL learner and explains the patterns in relation to first-language transfer and phonotactic adaptation. Methods: A descriptive qualitative design was used with one first-year senior high school student whose first language was Javanese. Data were collected in one session through word, phrase, and clause reading tasks, audio recording, and a semi-structured interview. The data were analyzed auditorily and descriptively by comparing broad Standard British English target forms with observed IPA realizations. Results: The data showed substitutions of /θ/ with [t] or [d], /ð/ with [d] or [t], and /v/ with [f], together with selected vowel and diphthong changes and vowel insertion in consonant clusters. However, several tokens containing the same target sounds were produced accurately, indicating that L1 influence was selective rather than absolute. Conclusions: Javanese phonology contributed to particular pronunciation patterns through sound substitution, syllable-structure adaptation, and possible orthographic influence. The findings support explicit pronunciation practice that prioritizes high-impact contrasts and develops production from isolated words to connected clauses.